MARKET PENETRATION STRATEGY AND COMPETITIVENESS OF MOBILE TELECOMMUNICATION SERVICE PROVIDERS IN KENYA - Gecheo, P. Ooga; Thuo, J. Kuria; Byaruhanga, J. (IJRDO - Journal of Business Management, 2016)
One of the most important questions faced by business leaders in the strategic management process is a choice of how to adopt a market penetration strategy whereby a firm gains more usage from existing customers and also seeks to attract customers from existing competitors. The mobile service industry has recently experienced a quick succession of mobile service innovations, in deciding on the optimal timing of each service launch, carriers need to consider a complex array of technological, regulatory, and strategic factors. In spite of wide-ranging research on market penetration strategy, very little empirical research has observed the relationship between the market penetration strategies and competitiveness in mobile telecommunication sector. Based on this background, this study sought to investigate market penetration strategy and competitiveness of mobile telecommunication service providers in Kenya.The study population consists of all the mobile Service providers in Kenya which according to a list obtained from Communications Commission of Kenya as at July 2010 are four. Given the small number of firms a census study was conducted. The data for this study was collected from primary sources using a semi-structured questionnaire. The findings of the study revealed market penetration strategy also correlates positively with organizational competitiveness. This study is significant since it is hoped that findings and recommendation of the study will provides a greater understanding of appropriate market penetration strategy implementation framework as well as how market penetration strategies influences organizational competitiveness. In this sense, the study will contributes to knowledge in terms of effective strategy implementation and its contribution to organizational performance.